Cell and molecular regulation of pancreas regeneration - Smid, Johnathan (University of Ottawa (Canada), 2009)
Although pancreatic regeneration has been well documented, the cellular source and inducing factors remain unknown. To elucidate the cellular source of regeneration cells from the adult resting pancreas expressing Stem cell antigen 1 (Sca1) were assessed as a candidate stem cell population. Sca1-expressing cells represented a heterogeneous population with only a very small percentage capable of differentiating to the beta-cell lineage. After expansion in culture Sca1-expressing cells lost their ability to differentiate and uniformly expressed the mesenchymal markers of activated pancreatic stellate cells (PSCs). To elucidate factors which stimulate regeneration the remnants following partial pancreatectomy (PPx) in adult C57BL/6J mice were examined. An early proliferation of mesenchymal cells producing a stroma was observed. Therefore, it was hypothesized that this mesenchymal stroma played a role in facilitating regeneration. Directly injecting mesenchymal cells into the pancreas of adult SCID-BEIGE mice was sufficient to induce pancreatic regeneration including tubular complex formation, ductal Pdx1 and Ngn3 expression. To determine specific factors that initiate the regeneration process a microarray screen was performed on the tip of the remnant following PPx. The secreted protein periostin was highly expressed in this regenerating tip. Injecting periostin directly into the pancreas stimulated the proliferation of resident mesenchymal cells to create a stroma. Following stromal formation, proliferating tubular complexes formed and both Ngn3 and Pdx1 were expressed. Periostin null mice had reduced stromal accumulation after PPx which impaired regeneration. Therefore, the formation of a mesenchymal stroma is necessary and sufficient for the induction of regeneration in the pancreas. Thus, inducing pancreatic regeneration by stimulating mesenchymal cells provides a novel approach for the treatment of diseases such as diabetes.
Keywords: Biology, Molecular.